FlOariasis caused by nonpedodic form of Brugia malayi among Bugis and Banjar settlers in East Kalimantan - FA Sudjadi, FA Sudjadi (Universitas Gadjah Mada, 1998)
Nonperiodic form of B. malayi was recently discovered as a new infraspecific variant (new subspecies) of filarial parasite found among Dayak Indigenous people living scattered in deep forest of East Kalimantan. In this research, clinical or blood (including membrane filter concentration method) examinations were carried out on Bugis or Banjar tribais in kampongs or more open areas in East Kalimantan. The malayan filariasis infections were detected among them, but not in high prevalence nor microfilarial density, such as found in two villages in Mahakam delta or another one In Bontang area, Kutai regency. The clinical manifestations, however, were not severe nor specific.Key words: Brugia malayi - nonperiodic form - Bugis and Banjar settler - natural selection pressure - parasite dispersal.